Designing English Reading Text Based on Dalihan Na Tolu Batak Culture - Yenita br Sembiring; Dewi Mariani; Wanti Elprida Purba; Ermin Avianti Amazihono; Elvira Rosyida MR (Jurnal Ilmiah Wahana Pendidikan, 2022)
Dalihan Na Tolu system is one element in the culture of Batak Toba. Dalihan Na Tolu is a system of kinship that is used as a basis and reference for the Batak Toba community within their social life. The Dalihan Na Tolu system contains statuses and roles. In determining social status, Batak Toba people first consider their lineage and clan. Outlined by Dalihan Na Tolu and established specific guidelines and laws for different social relationships such as those between a husband and wife, parents, and siblings from each party, additionally each party performed boru and hula-hula. Dalihan Na Tolu becomes the ideal form of kinship for the Batak people of Toba only if implemented in accordance with its principles. This research is descriptive qualitative research obtained through literature study, interview and observation data collection techniques. The material object of this study is the kinship system of the Batak Toba community. Based on the study is findings , it is known that dalihan na tolu dalam culture is the key in the implementation of marriage ceremonies. boru duties as part of the pretext na tolu in every marriage ceremony and other traditional ceremonies have been arranged. The Batak community has clear rules, who does what, who receives and gives what. Perfection of a traditional ceremony for the Batak people is measured by the completeness of the elements of the pretext na tolu to attend the ceremony women and her husband's group (boru) occupy a lower position while the giver of women (hula- hula) occupy a higher position. In this case, women become the object while men become the determining subject of one's position in the structure of dalihan na tolu